Utilization of Used Cardboard Waste As a Learning Resource to Improve Early Childhood Fine Motor Development - Meilina, Duwi; ismunandar, Arif; R, Rinovian; Mokodenseho, Sabil; Haris, Muhammad (CV. Creative Tugu Pena, 2022)
In the process of early childhood, fine motor development involves a variety of ways, including utilizing media for learning. We can get this media in the surrounding environment, such as used cardboard media, which can be utilized in the learning process for early childhood by making various patterns. The purpose of the research in this study was to determine how using cardboard media for children's fine motor development. This research uses a quantitative methodology, with the research sample conducted on RA teachers. This research shows an increase in fine motor development in early childhood after using learning resources through cardboard waste. Keywords: Cardboard Waste Media, Fine Motor Development, Early Childhood